Focus of attention influences quiet-eye behavior and movement patterns at varying skill levels in femal basketball players - Rienhoff, R.; Strauss, B.; Fischer, L.; Baker, J.; Schorer, J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
Different foci of attention have varying influences on different expertise levels in motor control situations (Wulf, 2007). On another level, the quiet eye period also affects motor performance and seems to differentiate between expertise and performance levels (Vickers, 2007). This study investigated the possible association of focus of attention and quiet eye as well as their interacting effect on throwing performance. Methods: Basketball experts, advanced players and novices (n = 9 per group) performed 40 free throws, subdivided in blocks of ten throws. The first block provided baseline data while in blocks two to four participants performed external focus, internal focus, and no-focus conditions in a counterbalanced order. Gaze behavior was captured by an eye tracking system. Throwing accuracy and quiet eye duration were measured. Results: Clear difference between skill groups could be revealed for throwing performance during baseline, F(2,24) = 42.3, p < .01, f = 1.88. The analysis of the counterbalanced blocks showed differences between groups, F(2,24) = 44.0, p < .01, f = 1.91. Additionally the repeated measure instruction revealed significant differences, F(2,48) = 3.63, p = .03, f = .39, but not for the interaction, Fs(2,24) = .71, p = .59, f = .24, 1-â = .64. For quiet eye duration, analysis of variance showed no significant differences between groups, F(2,24) = .88, p > .05, f = .29, 1- â =.32, nor for the interaction (group x instruction) Fs(2,24) = .51, p > .05, f = .22, 1-â = .55, but significant differences for instructions as repeated measures, F(2,24) = 5.91, p < .01, f = .53. The post-hoc showed significant shorter quiet eye duration for external instruction in comparison to both other conditions. Furthermore significant differences in quiet eye duration can be revealed for hits vs. misses, F(1,15) = 3.72, p = .04, f = .50, and further the interaction of hits with skill groups, Fs(1,15) = 2.80, p = .05, f = .61. Hits are in total longer, caused by differences in advanced players. Discussion: Our results show an influence of instruction on throwing performance, thus all skill levels performed worst under external instruction, what might be explained by personal preference (Weiss, Reber, & Owen, 2008). Furthermore the quiet eye period influences the throwing performance with longer quiet eye durations for hits in comparison to misses in the not yet automated advanced players. It seems that only in a specific skill level (advanced players) the interaction of quiet eye and focus of attention has influence on throwing performance.